3-month surgical outcomes of Implantable Collamer Lens implantation for myopic regression after laser vision correction surgeries: a retrospective case series - Byunghoon Chung (BMC, 2021)
Abstract Background To investigate the surgical outcomes of implantable collamer lens (ICL) implantation in eyes with residual myopia after primary laser vision correction (LVC) surgeries. Methods This study included patients who underwent ICL implantation and had a history of LVC surgery, including photorefractive keratectomy (PRK) or laser-assisted in situ keratomileusis (LASIK). Visual acuity and refractive error were assessed pre and 3-months postoperatively and the efficacy and safety indices calculated accordingly. Results A total of 30 eyes of 17 patients were included in this study. At 3 months, the mean logMAR uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), and spherical equivalent were − 0.03 ± 0.11 (include logMAR), − 0.04 ± 0.09 (include logMAR), and − 0.06 ± 0.33 diopters (D), respectively. The 3-month Snellen UDVA was better than 20/20 for 83% of eyes, and 97% of eyes showed an unchanged or improved CDVA after surgery. The mean efficacy and safety indices were 1.11 ± 0.22 and 1.13 ± 0.20, respectively. Further, 93 and 100% of eyes were within ±0.5 and ± 1.0 D of the attempted spherical equivalent refraction, respectively. Conclusions ICL implantation in eyes with myopic regression after previous LVC surgery showed safe, effective, and predictable outcomes. Trial registration retrospectively registered.